CXADR‐like membrane protein protects against heart injury by preventing excessive pyroptosis after myocardial infarction. Issue 23 (21st October 2020) - Han, Xinglong; Zhao, Zhen‐Ao; Yan, Shiping; Lei, Wei; Wu, Hongchun; Lu, Xing‐Ai; Chen, Yueqiu; Li, Jingjing; Wang, Yaning; Yu, Miao; Wang, Yongming; Zheng, Yufang; et al.
Abstract: Myocardial infarction (MI) results in cardiomyocyte death and ultimately leads to heart failure. Pyroptosis is a type of the inflammatory programmed cell death that has been found in various diseased tissues. However, the role of pyroptosis in MI heart remains unknown. Here, we showed that CXADR‐like membrane protein (CLMP) was involved in pyroptosis in the mouse MI heart. Our data showed that CLMP was strongly expressed in fibroblasts of the infarcted mouse hearts. The Clmp +/− mice showed more serious myocardial fibrosis and ventricular dysfunction post‐MI than wild‐type ( Clmp +/+ ) mice, indicating a protective effect of the fibroblast‐expressed CLMP against MI‐induced heart damage. Transcriptome analyses by RNA sequencing indicated that Il‐1β mRNA was significantly increased in the MI heart of Clmp +/− mouse, which indicated a more serious inflammatory response. Meanwhile, cleaved caspase‐1 and Gasdermin D were significantly increased in the Clmp +/− MI heart, which demonstrated enhanced pyroptosis in the Clmp knockdown heart. Further analysis revealed that the pyroptosis mainly occurred in cardiac fibroblasts (CFs). Compared to wild‐type fibroblasts, Clmp +/− CFs showed more serious pyroptosis and inflammatory after LPS plus nigericin treatment. Collectively, our results indicate that CLMP participates in the pyroptotic and inflammatory response of CFs in MI heart. We have provided a novel pyroptotic insight into the ischaemic heart, which might hold substantial potential for the treatment of MI.